Analisis Kemampuan TPACK Terintegrasi STEM Calon Guru SD Pembelajaran IPA dalam Menumbuhkan Nilai Edusciencetechnopreneur - Winda Purnama Sari; Iful Rahmawati Mega (CENDEKIAWAN, 2023)
The aim of the research is to explore the ability of prospective educators to master technology through STEM integrated TPACK skills in the natural science field to increase the value of integrated edusciencetechnopreneur. This step is to prepare prospective teachers to face the development of science and technology in the world of education during the transition period of the industrial revolution from 4.0 to 5.0. This research is a survey research with a quantitative approach, with the research subjects being students of the even semester PGSD Study Program for the academic year 2021/2022. The sampling technique used was cluster sampling. Collecting data using a questionnaire with a likert scale and portfolio of students or prospective teachers, student journals, and several other documents related to research. The data analysis technique used SEM through AMOS and descriptive analysis. The results of the analysis show that prospective elementary school teachers have implemented STEM-integrated TPACK in science learning 56%–75% have been carried out. The results of comparison of GOF with GOFI through SEM are categorized as fit and marginal, but the regression weight does not show a significant effect between the STEM-integrated TPACK variable on the value of integrated edusciencetechnopreneur.